Specific Features of Immune Response in Patients with Different Asthma Endotypes Following Immunization with a Conjugate Pneumococcal Vaccine - Anton M. Kostinov; Anna Yu. Konishcheva; Andrey D. Protasov; Mikhail P. Kostinov; Valentina B. Polishchuk; Alexander V. Zhestkov; Natalia E. Yastrebova; Aristitsa M. Kostinova; Zhanar Sh. Musagulova; Ekaterina V. Prutskova (Vaccines)
Background: Asthma is a heterogeneous disease characterized by variable bronchial obstruction, hyper-responsiveness, and inflammation. Evaluating the immunological changes following pneumococcal immunization in patients with different asthma endotypes is of great importance. This study aimed to evaluate the effects of PCV13 on the clinical parameters and the changes over time in the levels of the main cytokines in asthma patients. Methods: This was a single-center, open-label, non-randomized, prospective, cohort, controlled study of 31 patients aged 18 to 80 with a known diagnosis of asthma. The study subjects were given one injection of PCV13. Their clinical parameters and serum concentrations of certain Th1/Th2/Treg cytokines were assessed over a year following the vaccination. Results: Compared to the pre-vaccination period, there was an 81.5% reduction in the number of patients with asthma exacerbations (p < 0.001), a 76.5% increase in the number of patients free from hospitalization (p < 0.001), and an improvement in the level of asthma control. Positive changes were observed both in patients with T2-high and T2-low asthma; however, only those with T2-low asthma showed a significant improvement in the level of asthma control. Significant changes were reported for IFN-γ: its serum concentrations increased six weeks following the vaccination (p < 0.05), primarily in patients with T2-high asthma. Conclusions: In asthma patients, immunization with PCV13 was clinically effective, irrespective of the asthma endotype. Its clinical effects were accompanied by a reduction in the rates of exacerbations and hospitalizations and an increase in IFN-γ serum levels. This finding suggests that this cytokine plays an important role in restoring immune response in asthma patients.